2018
DOI: 10.5935/0103-507x.20180037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical attitudes and perceived barriers to early mobilization of critically ill patients in adult intensive care units

Abstract: ObjectiveTo investigate the knowledge of multi-professional staff members about the early mobilization of critically ill adult patients and identify attitudes and perceived barriers to its application.MethodsA cross-sectional study was conducted during the second semester of 2016 with physicians, nursing professionals and physical therapists from six intensive care units at two teaching hospitals. Questions were answered on a 5-point Likert scale and analyzed as proportions of professionals who agreed or disag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
42
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 24 publications
5
42
1
9
Order By: Relevance
“…In agreement with other reports, we identified patient instability, deep sedation and lack of nurses as the top three barriers against advanced mobilization targets [ 15 , 29 ]. In contrast to some reports [ 16 , 18 , 21 , 34 ], however, there was a similar perception regarding mobilization barriers in our scenarios among the surveyed professions. Garzon-Serrano [ 16 ] reported that physical therapists indicate hemodynamic instability as an obstacle to mobilization, but not renal replacement procedures.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In agreement with other reports, we identified patient instability, deep sedation and lack of nurses as the top three barriers against advanced mobilization targets [ 15 , 29 ]. In contrast to some reports [ 16 , 18 , 21 , 34 ], however, there was a similar perception regarding mobilization barriers in our scenarios among the surveyed professions. Garzon-Serrano [ 16 ] reported that physical therapists indicate hemodynamic instability as an obstacle to mobilization, but not renal replacement procedures.…”
Section: Discussioncontrasting
confidence: 82%
“…Garzon-Serrano [ 16 ] reported that physical therapists indicate hemodynamic instability as an obstacle to mobilization, but not renal replacement procedures. Berney et al [ 34 ] and Fontela et al [ 21 ] reported similar results, with physicians and nurses rating ventilation status as decisive when setting mobilization targets, while physical therapists perceived sedation state as critical for the decision. Berney explains these differences with varying responsibilities in the ICU team.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Finally, due to our persistent follow-up with non-responders, we had a very high response rate (85%), which optimizes the external validity [22]. Our response rate is similar or better than other surveys of ICU PTs reporting response rates from 22 to 87% [7, 53, 54].…”
Section: Discussionmentioning
confidence: 88%
“…Among the hypotheses are the organizational aspects of the units and the need for cooperation from the medical team, which are indispensable to the process. It is important to underscore that implementing initiatives to overcome the barriers to mobilization is a factor that still limits adherence by the multiprofessional team, highlighting the difference between evidence-based recommendations and what actually occurs in the ICU in terms of early mobilization [37,38].…”
Section: Discussionmentioning
confidence: 99%